105k views
0 votes
Solve the following:
a) 2(x + 3) = x -4
b) 4(5x - 2) = 2(9x + 3)

2 Answers

6 votes

Answer:

2x + 6 = x -4

Explanation:

a) 2(x + 3) = x -4

multiply 2 by x and 3 to get them out of the parentheses

2*x = 2x 2 * 3 = 6

2x + 6 = x -4

here is a little help so you can go on

User Ralph Bolton
by
5.2k points
5 votes

Answer:


\text{a) } 2(x + 3) = x -4


2x+6= x -4


2x+6-6= x -4-6


2x= x -10


2x-x= x -x-10


x=-10


\text{b) } 4(5x - 2) = 2(9x + 3)


20x - 8 = 18x+ 6


20x - 8+8 = 18x+ 6+8


20x = 18x+ 14


20x-18x = 18x-18x+ 14


2x = 14


$(2x)/(2) =(14)/(2) $


x=7

User JCarlosR
by
5.1k points